The role of miR-122-5p in negatively regulating T-box brain 1 expression on the differentiation of mouse bone mesenchymal stem cells. Issue 7 (3rd May 2017) - Yang, Yu; Shen, Zhaoliang; Sun, Wei; Gao, Shuang; Li, Yuanlong; Guo, Yue
Abstract : To achieve neuronal differentiation of mouse bone mesenchymal stem cells (bMSCs) into neuron-like cells and explore the role of miR-122-5p that may regulate T-box brain 1 ( Tbr1 ) expression during the induction. BMSCs were cultured and induced with butylated hydroxyanisole, retinoic acid (RA), basic fibroblast growth factor, and nerve growth factor in vitro . The cells were stained for neuron-specific enolase ( NSE ) and β-III-tubulin by immunocytochemistry/immunofluorescence. MiR-122-5p that may regulate Tbr1 expression was predicted by bioinformatics and identified using a Dual-Luciferase assay. The expressions of miR-122-5p and Tbr1 were determined by real-time PCR and western blot before and after the induction. After infection of miR-122-5p, the expressions of Tbr1, NSE, and tauons were measured. BMSCs showed a short spindle shape with a uniform distribution. After 14 days, the induced cells showed neuronal traits with a pyramidal appearance. TargetScan and miRanda showed that miR-122-5p was well complementary with the target site of the Tbr1 3′-untranslated region. Identified by the Dual-Luciferase assay, we found that miR-122-5p could inhibit Tbr1 expression by binding to its 3′-untranslated region. Furthermore, the expressions of Tbr1 mRNA and protein were decreased by real-time PCR and western blot. Overexpression of miR-122-5p downregulated the expressions of Tbr1, NSE, and tauons. MiR-122- 5p may negatively regulate Tbr1 expression to affect the differentiation of bMSCs into neuron-like cells.